Does corporate social responsibility moderate financial performance and firm size on firm value? - Nathania Lauren; Ilzar Daud; Helma Malini; Giriati Giriati; Arman Jaya (Trigin Publisher, 2023)
The global socio-economic crisis has prompted businesses and stakeholders to consider sustainable development initiatives. Protecting firm value through sustainability initiatives was critical to help firms survive the crisis. This study aimed to investigate the moderating effect of Corporate Social Responsibility (CSR) on the relationship between financial ratios, firm size, and firm value during the post-pandemic era, as this period was the best time to fix the firm’s management strategy. The research focused on manufacturing firms that are publicly traded on the IDX from 2021 to 2022. This research employed a purposive sampling method, resulting in a sample size of 38 firms. This analysis technique employed the Multiple Linear Regression. The findings showed that profitability impacts firm value while liquidity, firm size, and CSR insignificantly affect firm value. CSR, as a moderation reduced the impact of profitability on firm value; however, it does not moderate the effects of firm liquidity and firm size on firm value. During the post-pandemic period, various business sectors are navigating economic challenges by implementing strategies to boost sales and strengthen stock values. Therefore, many businesses deprioritize sustainable development because it might increase costs, reducing profits and firm value